Cystic Fibrosis Diagnosis and Protocols, Volume I: Approaches to Study and Correct CFTR Defects - Amaral, Margarida D.; Kunzelmann, Karl.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2011)
Despite the many milestones in cystic fibrosis (CF) research, progress towards curing the disease has been slow, and it is increasingly difficult to grasp and use the already wide and still growing range of diverse methods currently employed to study CF so as to understand it in its multidisciplinary nature.  Cystic Fibrosis: Diagnosis and Protocols aims to provide the CF research community and related researchers with a very wide range of high-quality experimental tools, as an easy way to grasp and use classical and novel methods applied to cystic fibrosis.  Volume I: Approaches to Study and Correct CFTR Defects focuses on the cystic fibrosis transmembrane conductance regulator (CFTR) and its expression, biogenesis, structure, and function in terms of the defects causing CF.  Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls.   Comprehensive and practical, Cystic Fibrosis: Diagnosis and Protocols will provide readers with optimal working tools to address pressing questions in the best technical way, while helping all of us, as a research and clinical community, to move faster hand-in-hand toward unravelling the secrets of this challenging disorder and cure it.
Introduction to Part I: The Relevance of CF Diagnostic Tools for Measuring Restoration of CFTR Function after Therapeutic Interventions in Human Clinical Trials -- High-Throughput Screening of Libraries of Compounds to Identify CFTR Modulators -- Repair of CFTR Folding Defects with Correctors that Function as Pharmacological Chaperones -- Use of Primary Cultures of Human Bronchial Epithelial Cells Isolated from Cystic Fibrosis Patients for the Pre-Clinical Testing of CFTR Modulators -- Design of Gene Therapy Trials in CF Patients -- Nasal Potential Difference Measurements to Assess CFTR Ion Channel Activity -- Measurement of Ion Transport Function in Rectal Biopsies -- Introduction to Part II: RNA Methods to Approach CFTR Expression -- Quantification of CFTR Transcripts -- Nonsense-Mediated mRNA Decay and Cystic Fibrosis -- Approaches to Study CFTR Pre-mRNA Splicing Defects -- Impact of MicroRNA in Normal and Pathological Respiratory Epithelia -- Genomic Approaches to Studying CFTR Transcriptional Regulation -- Introduction to Part III: Biochemical Methods to Study CFTR Protein -- Analysis of CFTR Folding and Degradation in Transiently Transfected Cells -- In Vitro Methods for CFTR Biogenesis -- Analysis of CFTR Interactome in the Macromolecular Complexes -- Methods to Monitor Cell Surface Expression and Endocytic Trafficking of CFTR in Polarized Epithelial Cells -- Segmental and Subcellular Distribution of CFTR in the Kidney -- Endocytic Sorting of CFTR Variants Monitored by Single Cell Fluorescence Ratio Image Analysis (FRIA) in Living Cells -- Introduction to Part IV: Biophysical Methods to Approach CFTR Structure -- CFTR Three-Dimensional Structure -- Molecular Modeling Tools and Approaches for CFTR and Cystic Fibrosis -- Biochemical and Biophysical Approaches to Probe CFTR Structure -- NMR Spectroscopy to Study the Dynamics and Interactions of CFTR -- Introduction to Part V: Assessment of CFTR Function -- Application of High-Resolution Single-Channel Recording to Functional Studies of Cystic Fibrosis Mutants -- Electrophysiological, Biochemical, and Bioinformatic Methods for Studying CFTR Channel Gating and Its Regulation -- CFTR Regulation by Phosphorylation -- How to Measure CFTR-Dependent Bicarbonate Transport: From Single Channels to the Intact Epithelium.
Keywords: Molecular biology; Human genetics; Laboratory medicine; Molecular Medicine; Human Genetics; Laboratory Medicine